Konsep Entitas Bagi Usaha Sampingan Ibu Rumah Tangga - Hartati Tuli (Fakultas Ekonomi Universitas Negeri Gorontalo, 2021)
The problem in this service activity is the lack of understanding, knowledge and skills of housewives in separating personal wealth and business property or in this case better known as the entity concept. The purpose of this service activity is to improve the understanding and skills of housewives in applying the entity concept in managing their side business. This service activity uses lecture, discussion and direct practic methods. The success of this activity was determined that most of the mothers who had a side business or about 85% of the participants who took part in this training activity understood and were able to apply the concept of a business entity to the management of their side business.